Some highligh problems on current status and recommendation to improve the performance of material sciences research institutes in Vietnam - Ngoc, Tran Hau; Thao, Pham Xuan; Ha, Nguyen Thi; Chien, Nguyen Ngoc; Thu Oanh, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
This paper will provide a brief summary of some important findings, problems to be adjusted and some recommendations to improve the performance by research and development (R&D) institutes in the field of materials science (MS) in Vietnam based on analytical and survey data in 2016 by Vietnam Center for Science and Technology Evaluation. From the review of various data sources, the authors selected the optimal option to determine the list of R&D organizations in MS field in Vietnam and conduct surveys at those organizations to collect data whether serving the current status. In addition to analyzing a number of key operational issues, this report provides some recommendations for improving the performance of R&D organizations in MS field - one of priority fields in S&T development strategy 2011-2020 and vision 2030. Code: 17051501